PERFORMANCE EVALUATION OF SUKOHARJO REGENCY DPRD MEMBERS IN 2021 - Wawan Pribadi; Istiatin Istiatin; Sudarwati Sudarwati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
The goal of this study was to evaluate whether the variables of flexibility, motivation, work stress, and rewards have a substantial effect on employee performance. Additionally, to determine whether a significant concurrent influence exists and which variables are most influential in determining employee performance for members of the Sukoharjo Regency DPRD. The descriptive quantitative technique was utilized. The population in this study consisted of 43 employees, and the total population was sampled using quota sampling. Primary and secondary data were collected using the following techniques: observation, documentation, questionnaires, and literature review. Multiple linear tests were employed to analyze the data in this study. The study's findings indicate that: The study's findings indicate that: 1) Flexibility, motivation, work stress, and rewards all have an effect on employee performance at DPRD members of Sukoharjo Regency; 2) Flexibility has an effect on employee performance at DPRD members of Sukoharjo Regency; 3) Motivation has an effect on employee performance at DPRD members of Sukoharjo Regency; and 4) Work stress has an effect on employee performance at DPRD members of Sukoharjo Regency.